Dopamine D2 and D3 Receptors in Human Putamen, Caudate Nucleus, and Globus Pallidus - Gmeiner, Peter; et al. (Synapse, 2006)
Because radioactive raclopride and radioactive (+)-4-propyl-9- hydroxynaphthoxazine ((+)-PHNO) are used to image dopamine (DA) D2 and D3 receptors in the striatum and globus pallidus in humans, the present study examined the proportions of D2 and D3 receptors in postmortem tissues from these regions. Conflicting results were obtained when using a single concentration of remoxipride to occlude D2 receptors or using a single concentration of U99194A or FAUC 365 to occlude D3 receptors. However, using a range of concentrations of FAUC 365, a D3-selective antagonist, to inhibit the binding [ 3H]raclopride or [3H]-(+)-PHNO to D3 receptors at low concentrations (1-10 nM) and to inhibit ligand binding to D2 receptors at higher concentrations (100-2000 nM), it was possible to measure the proportion of D2 and D3 receptors in the tissues. This method revealed that these two radioligands detected only D2 receptors in the dorsal putamen and the dorsal caudate nucleus, but detected a mixed population of two-thirds D2 and one-third D3 DA receptors in the ventral putamen, the ventral caudate, and the globus pallidus. The present findings are in good agreement with the known gene expression data for D2 and D3 receptors in these human brain regions. © 2006 Wiley-Liss, Inc.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.lphch.dopami
Keywords: D2 receptor occupancy; Human basal ganglia; Imaging dopamine receptors; Schizophrenia